Use of cumaru as a medicinal plant: literature review - Ribeiro, Frances (2021)
At all times, men had the need to face the emergence of symptoms in their daily lives, due to trauma, use of new foods or illness. Aiming at cure, man used medicinal plants. These, in turn, represent the oldest “weapons” used by humanity to treat various illnesses, that is, the use of plants in the prevention and/or cure of diseases is a practice that has always existed in human history. Amburana cearensis A.C. Smith, belongs to the family of Leguminoseae Papilionoideae (Fabaceae), is a leafy tree, typical of the caatinga, especially in Ceará, where it is known as imburana-de-cheiro, cherry and cumaru. This plant is widely used by industries that make essential oils, perfumes, cosmetics, medicines, food, tobacco and beverages, for its aromatic and therapeutic properties. This research aimed to present the use of the plant Amburana cearensis A.C. Smith and it medicinal benefits. Introducing to the reader the benefits of this plant, exposing the pharmacological aspects of Amburana cearensis, o it has expressive health properties. The data presented in this review show that Amburana cearensis is considerably rich in compounds such as coumarins, flavonoids and phenolic glycosides, which support its populares use as a bronchodilator, analgesic and anti-inflammatory. It also showed that all parts of the plant contain compounds that can be used for benefits to man, and that not only adult trees can be used for this purpose, but also those cultivated with little time.